Monitoring workload in throwing-dominant sports: A systematic review - Black, G. M.; Gabbett, T. J.; Cole, M. H.; Naughton, G. (Sports Medicine, 2016)
Background: The ability to monitor training load accurately in professional sports is proving vital for athlete preparedness and injury prevention. While numerous monitoring techniques have been developed to assess the running demands of many team sports, these methods are not well suited to throwing-dominant sports that are infrequently linked to high running volumes. Therefore, other techniques are required to monitor the differing demands of these sports to ensure athletes are adequately prepared for competition. Objective: To investigate the different methodologies used to quantitatively monitor training load in throwing-dominant sports. Methods: A systematic review of the methods used to monitor training load in throwing-dominant sports was conducted using variations of terms that described different load-monitoring techniques and different sports. Studies included in this review were published prior to June 2015 and were identified through a systematic search of four electronic databases including Academic Search Complete, CINAHL, Medline and SPORTDiscus. Only full-length peer-reviewed articles investigating workload monitoring in throwing-dominant sports were selected for review. Results: A total of 8098 studies were initially retrieved from the four databases and 7334 results were removed as they were either duplicates, review articles, non-peer-reviewed articles, conference abstracts or articles written in languages other than English. After screening the titles and abstracts of the remaining papers, 28 full-text papers were reviewed, resulting in the identification of 20 articles meeting the inclusion criteria for monitoring workloads in throwing-dominant sports. Reference lists of selected articles were then scanned to identify other potential articles, which yielded one additional article. Ten articles investigated workload monitoring in cricket, while baseball provided eight results, and handball, softball and water polo each contributed one article. Results demonstrated varying techniques used to monitor workload and purposes for monitoring workload, encompassing the relationship between workload and injury, individual responses to workloads, the effect of workload on subsequent performance and the future directions of workload-monitoring techniques. Conclusion: This systematic review highlighted a number of simple and effective workload-monitoring techniques implemented across a variety of throwing-dominant sports. The current literature placed an emphasis on the relationship between workload and injury. However, due to differences in chronological and training age, inconsistent injury definitions and time frames used for monitoring, injury thresholds remain unclear in throwing-dominant sports. Furthermore, although research has examined total workload, the intensity of workload is often neglected. Additional research on the reliability of self-reported workload data is also required to validate existing relationships between workload and injury. Considering the existing disparity within the literature, it is likely that throwing-dominant sports would benefit from the development of an automated monitoring tool to objectively assess throwing-related workloads in conjunction with well-established internal measures of load in athletes.